Graphic design discourse : evolving theories, ideologies, and processes of visual communication - Kim, Henry Hongmin; Geissbuhler, Steff, 1942- (2018)
"Since its inception, the field of graphic design--whose primary aim is visual communication--has struggled between two contradictory poles: design resulting from a rigorous, fixed set of rules, and design that expresses the hand of the artist. But what if designers focused on process and critical analysis over visual outcome? Through a carefully selected collection of more than seventy-five seminal texts spanning centuries and bridging the disciplines of art, architecture, design history, philosophy, and cultural theory, this illuminating anthology establishes a new paradigm for graphic design methodologies for the twenty-first century"--
Includes bibliographical references (pages 450-455).
Keywords: Visual communication -- Methodology; Graphic arts -- Methodology; DESIGN / General; DESIGN / Graphic Arts / General; DESIGN / Essays